Transcranial ultrasound stimulation promotes brain-derived neurotrophic factor and reduces apoptosis in a mouse model of traumatic brain injury - Wei-Shen Su (Brain Stimulation, 2017)
Background: The protein expressions of brain-derived neurotrophic factor (BDNF) can be elevated by transcranial ultrasound stimulation in the rat brain. Objective: The purpose of this study was to investigate the effects and underlying mechanisms of BDNF enhancement by low-intensity pulsed ultrasound (LIPUS) on traumatic brain injury (TBI). Methods: Mice subjected to controlled cortical impact injury were treated with LIPUS in the injured region daily for a period of 4 days. Western blot analysis and immunohistochemistry were performed to assess the effects of LIPUS. Results: The results showed that the LIPUS treatment significantly promoted the neurotrophic factors BDNF and vascular endothelial growth factor (VEGF) at day 4 after TBI. Meanwhile, LIPUS also enhanced the phosphorylation of Tropomyosin-related kinase B (TrkB), Akt, and cAMP-response element binding protein (CREB). Furthermore, treatment with LIPUS significantly decreased the level of cleaved caspase-3. The reduction of apoptotic process was inhibited by the anti-BDNF antibody. Conclusions: In short, post-injury LIPUS treatment increased BDNF protein levels and inhibited the progression of apoptosis following TBI. The neuroprotective effects of LIPUS may be associated with enhancements of the protein levels of neurotrophic factors, at least partially via the TrkB/Akt-CREB signaling pathway.